Insights Into Nickel Slag Carbonation in a Stirred Bead Mill - Julcour, Carine; Cassayre, Laurent; Benhamed, Imane; Diouani, Jaouher; Bourgeois, Florent (Frontiers in Chemical Engineering, 2020)
This work is part of the ongoing development of the attrition-leaching carbonation process, a single-step aqueous carbonation technology that integrates a stirred bead mill. The principle of the attrition-leaching carbonation process is to continuously refresh the surfaces of reactive particles so that leaching can proceed unimpeded, yielding enhanced carbonation kinetics and yield. Invariably, attrition-leaching carbonation experiments carried out under controlled temperature and CO2 partial pressure conditions with different silicate-rich carbonation feedstocks - natural ores and nickel slags - show a carbonation yield that tends towards a plateau 20 to 50% below the stoichiometric yield. This repeatable behaviour raises the question as to whether the carbonation limitation is due to specific equilibrium side reactions of the carbonation feedstock or to a kinetic limitation of the attrition-leaching carbonation process. To try to provide some answers to this puzzling question, this reflexive paper implements a “thermo-kinetic” modelling methodology based upon geochemical equilibrium simulations and particle reaction models. The results obtained indicate that the observed slowing down of the carbonation process can be explained either by the formation of Mg- and/or Fe-rich silicates that precipitate at the expense of carbonates, or by a decrease in the efficiency of the attrition process over time. Indeed, either one of these mechanisms could explain the observed behaviour of the attrition-leaching carbonation process. However, the cross comparison of different data sources pleads in favour of the attrition-leaching carbonation performance being limited by the attrition process. Pending further confirmation, this tentative conclusion suggests that further development of the attrition-leaching carbonation process requires new knowledge about its inner workings, and that there may be ways to optimize the performance of this process beyond that based on standard stirred bead mill operating rules.